2015
DOI: 10.1111/epi.13271
|View full text |Cite
|
Sign up to set email alerts
|

Epilepsy with temporal encephalocele: Characteristics of electrocorticography and surgical outcome

Abstract: Temporal lobe encephaloceles (TEs) are increasingly identified in patients with epilepsy due to advances in neuroimaging. Select patients become seizure-free with lesionectomy. In practice, however, many of these patients will undergo standard anterior temporal lobectomy. Herein we report on the first series of patients with refractory temporal lobe epilepsy (TLE) with encephalocele to undergo chronic or intraoperative electrocorticography (ECoG) in order to characterize the putative epileptogenic nature of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
95
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(104 citation statements)
references
References 15 publications
7
95
0
2
Order By: Relevance
“…This study emphasize, along with other two new studies, 13,14 the recent interest in small temporal encephaloceles as a significant cause of temporal lobe epilepsy in patients in whom MRI was read as normal or noninformative. In contrast with previous studies, [5][6][7][8][9][10][11][12][13][14] we have focused our study in patients with encephaloceles that are located at the tip of the temporal pole. Therefore, we were able to gather a homogenous cohort that potentially shared similar features, Semantic tests results are shown for a selected group of patients (n = 12) and for a group of control healthy subjects (n = 17).…”
Section: Discussionsupporting
confidence: 73%
See 4 more Smart Citations
“…This study emphasize, along with other two new studies, 13,14 the recent interest in small temporal encephaloceles as a significant cause of temporal lobe epilepsy in patients in whom MRI was read as normal or noninformative. In contrast with previous studies, [5][6][7][8][9][10][11][12][13][14] we have focused our study in patients with encephaloceles that are located at the tip of the temporal pole. Therefore, we were able to gather a homogenous cohort that potentially shared similar features, Semantic tests results are shown for a selected group of patients (n = 12) and for a group of control healthy subjects (n = 17).…”
Section: Discussionsupporting
confidence: 73%
“…In addition to other studies, [5][6][7][8][9][10][11][12][13][14] which mainly described the epilepsy found in patients with RFE, we also included patients with well-controlled epilepsy. In doing so we broaden the clinical spectrum associated to this type of lesion.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations